Estudo das alterações retinianas em olhos de coelhos após injeções intravítreas seriadas de infliximabe - RASSI, Alan Ricardo (2011)
The objective of this study was to determine the levels of toxicity of two and three intravitreous injections of infliximab to the retina and choroid of albino rabbits by means of histological, electroretinographic and clinical ophthalmological tests. Twelve New Zealand albino rabbits (24 eyes) were used in the study. Each eye was given two (n=10) or three (n=10) serial intravitreous 2 mg injections of infliximab dissolved in 0.06 ml of saline, at monthly intervals. A separate group of rabbits (n=4 eyes) served as a control group. Ninety days after the first injection, the rabbits underwent electroretinographic and clinical ophthalmological tests. After being enucleated, the eyes underwent histological examination. No clinical ophthalmologic abnormalities were detected in the 24 eyes studied. The histological change noted was the presence of rare lymphocytes and eosinophiles in the posterior vitreous of four eyes subjected to two injections and six eyes subjected to three injections of infliximab, but it was not considered clinically significant. One clinically significant abnormality was found, a severe inflammatory reaction with vitreous exudates and ganglion cell edema in both eyes of a single rabbit, subjected to two to three injections of infliximab. The electroretinographic tests showed amplitudes that were on the average 12% smaller than those obtained before the treatment. However, there were no statistically significant differences when comparing amplitude or the implicit time between the pre and post-treatment electroretinographic findings, in all groups examined. Then, two and three intravitreous 2 mg injections of infliximab in eyes of rabbits at monthly intervals did not cause any changes after a 90-day follow-up, according to histological, electroretinographic tests and clinical ophthalmological evaluation. It was concluded that serial intravitreous infliximab doses to rabbits is a safe procedure.